Зміна експресії репаративного ензиму MGMT та білка MARP при спільній дії цитокіну IFNα2b та алкілувальної сполуки MNNG на клітини людини in vitro - Акуленко, О.А.; Коцаренко, К.В.; Лило, В.В.; Черних, С.І.; Лукаш, Л.Л. (Фактори експериментальної еволюції організмів, 2016)
Aim. To study the effect of IFN-α2b and alkylating agent MNNG on the amount of O6 -methylguanine-DNA methyltransferase (MGMT) protein in human cells in vitro. Methods. The human cells of Hep-2 line were treated with the purified recombinant protein IFN-α2b and alkylating agent MNNG. Changes in the MGMT gene expression were studied at a protein level by Western blot analysis. Results. Joint application of IFN-α2b and MNNG, as well as the separate ones, led to the growth of MGMT and MARP (anti-Methyltransferase Antibody Recognizable Protein) amounts The most significant increase of studied proteins expression was observed during joint application of MNNG (0.1 μg/ml and 0.5 μg/ml) in combination with IFN-α2b at 2 IU/ml (for MGMT and MARP respectively). Conclusions. IFN-α2b and MNNG caused increasing MGMT and MARP amounts in all studied concentrations from 31 to 86% compared to the intact control. Keywords: human cells in vitro, MGMT, MARP, cytokine IFN-α2b, alkylating agent MNNG.